Estrategias de afrontamiento tras una ruptura de relaciones afectivas en jóvenes adultos de la carrera de Ciencias de la Comunicación Social del Área de la Educación, Arte y Comunicación, de la Universidad Nacional de Loja, mayo-junio 2015 - Jaramillo Bustamante, María Emilia (2015)
The present investigation has as intention determine the strategies of confrontation used by a group of young people before the break up a relationship; as well inquire the reasons and effects that generate this situation. For it, there was gathered information of 116 young adults, men and women, of the Career of Comunicacion Social of the Area de la Educacion, Arte y Comunicacion of Universidad Nacional de Loja. In the development of this study a survey designed by the investigator was used, it was very helpful for the compilation of information, the Questionnaire called: Reacciones Psicológicas a la Separación (Montilla), and the Questionnaire: Cuestionario de Afrontamiento COPE (Castilian Adjustment, 1997). Once applied the instruments of investigation we knew that were some significant differences between men and women about the strategies of confrontation used to approach the experience of breaking up. So we conclude that 17% the women use more the religion, being this style of confrontation centered on the emotions; whereas that 17% the men use some distracting activities, referenced to an avoidant style; those kinds of confrontation are not adaptive because, they reduce the emotional discomfort in the first moment. As well it can be noticed that the effects of the break are presented in the form of depressive and anxious symptoms, if we do not treat those reactions they could become some psychopathological disorders. Due to the fact that it was a possibility of emotional alterations we design an intervention plan, focused to improving the psychological well-being. Keywords: relationship breakdown, coping strategies, young adults.